Mesoscale Horizontal Kinetic Energy Spectra of an Eastward-Moving Southwest Vortex - Shiwang Yu; Lifeng Zhang; Yuan Wang; Jun Peng (Atmosphere, 2022)
A high-resolution simulation with the Weather Research and Forecasting (WRF) model is performed to investigate the characteristics of the horizontal kinetic energy (HKE) spectra of an eastward-moving southwest vortex (SWV) generated in Sichuan Province, China, during 16–19 June 2011. The results indicate that the evolution of the SWV can be divided into the development, mature, and decay stages. In the troposphere, the HKE spectrum reproduces the typical atmospheric spectrum, with a slope of approximately −3 for wavelengths greater than 300 km and −5/3 for wavelengths between 300 and 30 km in each stage. The average scale of spectral transition is around 300 km. However, the HKE spectrum in the lower stratosphere shows a −5/3 slope at mesoscales and has no clear spectral transition. During the mature stage of the SWV, the HKE increases prominently for wavelengths between 300 and 30 km. Moreover, the relative contribution of the rotational kinetic energy (RKE) and the divergent kinetic energy (DKE) was investigated. It shows that the RKE spectrum dominates the DKE spectrum for wavelengths greater than 300 km in the lower troposphere, while in the upper troposphere the magnitudes of RKE and DKE are comparable over all scales. However, in the lower stratosphere, the DKE is an order of magnitude larger than the RKE, contributing more to the total HKE spectrum.